Islamic Banking System and Economic Growth: Exploration of D-8 Countries - Hamadou, Issa (Universitas Islam Internasional Indonesia, 2022)
The aim of this investigation is to look at the effect of the Islamic banking system on the economic growth of D-8 countries as well as their relationship and the causality direction. Annual report time series data were used from 2010–2021. Islamic Banking Financing (IBF) was used as a representation of the Islamic banking sector, while Foreign Direct Investment (FDI), Gross Fixed Capital Formation (GFCF), Gross Domestic Product (GDP), and Trade were used to represent the economic sector. The econometric tools used are the panel unit root test, panel test of cointegration, and the causality test of Granger. The findings showed that, in the short and long run, Islamic banking and economic growth have a positive connection in D-8 countries. Moreover, there is bi-directional causality. That means, there is a two-way causality starting from the growth sector to Islamic banking and Islamic banking to economic growth. It is also discovered that, in the short run, investment (GFCF) and trade activities have an affirmative influence on the development of Islamic banking. Increasing investment formation will thus successfully subsidize the expansion of the Islamic banking segment of D-8 countries. However, the main policy implication is that governments of the D-8 countries can support economic growth by expanding the finance sector through additional liberalization measures. It is recommended to include another variable that is currently not used, such as the quality of the institutions, and moreover, to apply other statistical tools such as ARCH and GARCH to look at profound relationships.